A salvage journey from true transverse colon volvulus, a rare cause of large bowel obstruction: a case report - Sarker, Rajib Dey; Akther, S M Quamrul Akther; Reza, Syed Masud; Hannan, Sheikh Mohammad Abdul Hannan; Salehin, Sadique; Mannan, Mubina Binte; Shama, Anika Ibnat; Shaily, Suchi (Faridpur Medical College Journal, 2026)
Background: In brief, the colonic volvulus has the rarest presentation in transverse colon due its anatomical idiosyncrasy and obvious superiority with other portions of the colon. However, transverse colon volvulus presents with symptoms and signs indicative of obstruction in the large bowel. Typically, this condition is diagnosed during surgery. Ironically, it is a surgical emergency that can compromise the gut viability as well as patient’s life. Case presentation: We present a unique case of transverse colon volvulus in a 46-year-old male patient with no notable medical or surgical history. Patients presented with all the symptoms of long-standing bowel obstruction and was resuscitated and operated to honour every moment of gut viability. This colonic volvulus is notified in only a few cases reported literature, we hereby report this case for meticulous understanding. Conclusion: Transverse colon volvulus is exceedingly uncommon but crucially fatal in surgical scenarios. Delaying surgery any longer would have jeopardized this patient's survival. When confronted with symptoms of large bowel obstruction, transverse colon volvulus should be included in the list of potential diagnoses. Prompt diagnosis and intervention significantly enhance the patient's outcome. Given its rarity, a heightened level of suspicion and awareness are essential for accurate diagnosis. Faridpur Med. Coll. J. 2026;21(1):58-63